2022
DOI: 10.1039/d1nr07152a
|View full text |Cite
|
Sign up to set email alerts
|

Sequential structural degradation of red perovskite quantum dots and its prevention by introducing iodide at a stable gradient concentration into the core–shell red perovskite quantum dots

Abstract: Perovskite quantum dots (QDs) have been extensively studied as emissive materials for next-generation optoelectronics due to their outstanding optical properties; however, their structural instabilities, specifically those of red perovskite QDs,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…1,2 Recent studies demonstrated that defect engineering can effectively tune the microstructure of materials, making them suitable for multi-domain applications, especially in photocatalysis. [3][4][5][6] Among many defect structures, zero-dimensional point defects (atom vacancy) have a more sensitive effect on the microstructure of materials. [7][8][9] Even if there is one atom vacancy in one hundred million host atoms, the electronic structure of the material will change intensely.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Recent studies demonstrated that defect engineering can effectively tune the microstructure of materials, making them suitable for multi-domain applications, especially in photocatalysis. [3][4][5][6] Among many defect structures, zero-dimensional point defects (atom vacancy) have a more sensitive effect on the microstructure of materials. [7][8][9] Even if there is one atom vacancy in one hundred million host atoms, the electronic structure of the material will change intensely.…”
Section: Introductionmentioning
confidence: 99%
“…It has a good application prospect in light emitting diode, photo detector, solar cell, laser and other fields. [ 1–7 ] In particular, the CsPbX 3 (X = Br, Cl, I) PQDs are considered to be a promising luminescent material. However, the poor stability to air, temperature, especially water, which seriously limits their practical application in the field of optoelectronic.…”
Section: Introductionmentioning
confidence: 99%
“…It has a good application prospect in light emitting diode, photo detector, solar cell, laser and other fields. [1][2][3][4][5][6][7] In particular, the CsPbX 3 (X = Br, Cl, I) PQDs are considered to be a promising luminescent material. However, the poor stability to air, temperature, especially water, which photoluminescence (PL) intensity remained at 60% after 24 h. Compared with CsPbBr 3 PQDs synthesized by OA as a surface ligand, the PL intensity decreased to <1% after only 1 h. This method can also improve the stability of CsPbCl 3 and CsPbI 3 PQDs in water.…”
Section: Introductionmentioning
confidence: 99%
“…However, Br atoms are prone to migrating and generating surface defects during the purification process, causing the crystal structure of the perovskite QDs to transition to the orthorhombic phase. Consequently, most perovskite QDs after purification consist of both cubic and orthorhombic phases . Pristine perovskite QDs are more susceptible to transition from cubic to orthorhombic due to surface ligand dissociation in the solution state, leading to rapid PL loss in ambient conditions.…”
mentioning
confidence: 99%
“…Consequently, most perovskite QDs after purification consist of both cubic and orthorhombic phases. 13 surface ligand dissociation in the solution state, 14 leading to rapid PL loss in ambient conditions. Core−shell perovskite QDs effectively reduce the generation of surface defects via ligand dissociation, thereby remarkably reducing the occurrence of a phase transition during the purification process or storage in ambient conditions.…”
mentioning
confidence: 99%